Pemetaan Bibliometrik terhadap Perkembangan Penelitian E-Learning pada Google Scholar Menggunakan Vosviewer - Habibi, Fajri; Fitriana, Ana; Sulityowati, Endar (Attractive : Innovative Education Journal, 2022)
This article aims to examine the development of e-learning (electronic learning) in the last 11 years. This research was also carried out to find out trends in e-learning research, identify relationships between scientific concepts, and find out e-learning networks based on keywords (co-occurrence) and author collaboration (co-authorship). The method used in this research is descriptive bibliometric analysis, the data used was taken from 2010-2021. Data collection was carried out based on the Google scholar database with the keyword e-learning with a publication limit of 1,000 journal articles. Data collection was carried out using Publish or Perish (PoP) software as metadata. Data analysis was performed using Vosviewer software as a medium for bibliometric analysis. The results showed that in the last 11 years the number of publications on information architecture research indexed by Google Scholar has fluctuated, but in terms of quantity it has increased significantly. The highest publication growth development occurred in 2020, reaching 102 journal articles (10.2%), while the lowest publication occurred in 2019 with a total of 53 journal articles (5.3%). While mapping the development of information architecture research publications based on keywords (co-occurrence) indicates a relationship between e-learning concepts accompanied by 6 dominant clusters, although this research has not been widely researched, research in the field of e-learning can foster research opportunities with topics unrelated topics. Keywords: E-Learning Google Scholar, Development of E-Learning Research, Bibliometric Mapping